Effectiveness of Endophyte Fungi as a Controling of Blast Disease on Paddy (Oryza sativa) : EFEKTIVITAS CENDAWAN ENDOFIT SEBAGAI PENGENDALI PENYAKIT BLAST PADA TANAMAN PADI (Oryza sativa) - Sopialena; Devi Tantiani (Agrifarm : Jurnal Ilmu Pertanian, 2020)
The research was conducted to determine: endophyte fungi on paddy plant (Oryza sativa); the antagonistic percentageof endophyte fungi against to Pyricularia oryzae Cav.; and the antagonistic mechanisms between each endophyte fungi to Pyricularia oryzae Cav..The experiment was conducted at the Integrated Laboratory of Agriculture Faculty of Mulawarman University, and samples of infected plant was collected from Sungai Kapih village, Sambutan Sub-district of Samarinda City The experimental treatments was arranged in a Completely Randomized Design (CRD), consisting of four treatments and each treatment was repeated ten times.The results showed that endophyte fungi isolated from the paddy plant (Oryza sativa) were Trichoderma sp., Rhizopus sp., Gliocladium sp., and Penicillium sp. The competition was proved as the antagonistic mechanism of Rhizopus sp. against, while antibiosis was proved as the antagonistic mechanism of Penicillium sp. against. Trichoderma sp. and Gliocladium sp. against were shown to have two antagonistic mecanism are competition and parasitsm. The capability of endophyte fungi as a biological agents to compete those P. Oryzae was express an antagonism capacity differences, the highest rate of inhibition was occurred on the P. oryzae vs Gliocladium sp.(78,96%). Keywords :Pyricularia oryza Cav., Endophyte fungi, Antagonistic mechanim